Effect of carbon fiber oxidization parameters and sizing deposition levels on the fiber-matrix interfacial shear strength. (November 2018) - Stojcevski, Filip; Hilditch, Timothy B.; Gengenbach, Thomas R.; Henderson, Luke C.
Abstract: This paper investigates fifteen fiber types against two epoxy resin systems and the effects of altering electrochemical oxidization conditions and sizing deposition ratio on interfacial shear strength (IFSS). Oxidization current was altered between 0, 2, and 3.4 A while sizing deposition ratio was altered between unsized, 1:10, 1:15 and 1:20 parts sizing to water. Desized fibers were also compared against pristine unsized fibers. Results show, a correlation between increasing current and IFSS, however sizing has an optimal ratio for best performance. Improvements through oxidization are attributed to the introduction of oxygenated functional groups on the fiber surface while improvements due to sizing are attributed to the promotion of a chemically active intermediate layer between the fiber and resin. Fiber roughness was seen to play no effect on IFSS. Desized fibers and unsized fibers had similar IFSS results however characterisation shows chemical composition of the fiber surfaces to be very different.